2018
DOI: 10.1039/c8ra07064d
|View full text |Cite
|
Sign up to set email alerts
|

Friction-induced selective etching on silicon by TMAH solution

Abstract: Friction-induced selective etching by TMAH solution was proposed for patterning a silicon surface with site control, high flexibility and low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Accordingly, etching rate in scratched regions was slow down, resulting in the formation of hillock nanostructures. Similar performance and mechanisms were assigned on the friction-induced selective etching on silicon surface when TMAH solution was employed [67].…”
Section: Mechanisms For Scratch Masking In Friction-induced Selectivementioning
confidence: 60%
See 2 more Smart Citations
“…Accordingly, etching rate in scratched regions was slow down, resulting in the formation of hillock nanostructures. Similar performance and mechanisms were assigned on the friction-induced selective etching on silicon surface when TMAH solution was employed [67].…”
Section: Mechanisms For Scratch Masking In Friction-induced Selectivementioning
confidence: 60%
“…It is found that fabrication width was effectively controlled by the normal load, while fabrication height almost remained to stable after the scratches produced under contact pressure beyond 6.3 GPa were etched by KOH solution [27,56]. Zhou et al also found that the fabrication height is irrelevant with normal load during friction-induced selective etching in TMAH solution as long as the mask was active [67]. The fabrication height was both closely related with etching time in the two anisotropic etchants, i.e., KOH and TMAH solution, and the difference in etching time-dependent selective etching was attributed to subsurface deformation induced by diamond tip with different curvature radii.…”
Section: Effects Of Normal Load and Etching Time On Friction-induced mentioning
confidence: 99%
See 1 more Smart Citation
“…Wet etching is regarded as a promising alternative approach due to its simple, flexible and low-cost features. However, the directional etchants used in silicon etching, including alkali metal hydroxides (NaOH, KOH), [17,26] amino hydroxide (NH 4 OH, (CH 3 ) 4 NOH) [27], and ethylenediamine/catechol/water mixtures (called EDP or EPW) [28], are based on the selective etching for specific crystal faces (such as Si(100) and Si(110)). Namely, the etching rate in one crystal face is much faster than that in other directions (such as Si(111) is the so-called etching 'stop plane') [29].…”
Section: Introductionmentioning
confidence: 99%